Strategies and Representation Employed by Primary School Students in a Functional Relationship: A Focus on Generalization Process - Sugianto, Andi; Rosjanuardi, Rizky; Lukman, Lukman (Jurnal Pendidikan MIPA, 2024)
This investigation endeavours to investigate the strategies and representations employed by primary school students in the process of generalising patterns.. The research design employed to accomplish the objectives of this study is a case study design that explores the functional thinking of students. Data were collected from 16 students grade 5 primary school students through written tests related to generalizing pattern and interviews. Subsequent procedures involved interviewing 4 representative students to obtain comprehensive information regarding their responses to the written test. Students who used the recursive strategy focused on changing one quantity and could not make generalizations and students who used the correspondence strategy managed to build generalizations between pairs of corresponding variables and could use the generalization results appropriately. Students produce two categories of representations when generalizing a pattern. The majority of them employed verbal representation to represent the generalization, while the remainder employed pictorial representation. The research concludes that these distinctions are the result of their emphasis on pattern identification: students who observe recursive patterns are more likely to observe changes in a single variable, while correspondence patterns are associated with the corresponding pair of variables.      Keywords: recursive patterns, correspomdence, functional relationship, representation, generalization. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp2013-2028